2003
DOI: 10.1038/sj.bjc.6600682
|View full text |Cite
|
Sign up to set email alerts
|

Foscan® uptake and tissue distribution in relation to photodynamic efficacy

Abstract: Clinical photodynamic therapy (PDT) schedules are based on the assumption that optimum drug -light intervals are times at which there is a maximum differential between photosensitiser retention in the tumour and surrounding normal tissue. However, vascularmediated effects contribute to tumour destruction by PDT; therefore, plasma sensitiser levels and endothelial cell drug exposure could also be important determinants of PDT response. The purpose of this study was to investigate the influence of tumour, tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 21 publications
(29 reference statements)
10
105
1
3
Order By: Relevance
“…There is also a high initial retention in the vasculature that is confirmed by initial volume of the distribution (32.0 ml kg À1 ), which is small compared to the blood volume of a rat (50 -70 ml kg À1 ). m-Tetra (hydrophenyl)chlorin may be initially retained in the vascular system, possibly due to protein binding or precipitation (Clark and Smith, 1986). This is consistent with plasma binding studies with m-THPC that shows an unusual initial protein-binding pattern for a hydrophobic photosensitiser (Hopkinson et al, 1999).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…There is also a high initial retention in the vasculature that is confirmed by initial volume of the distribution (32.0 ml kg À1 ), which is small compared to the blood volume of a rat (50 -70 ml kg À1 ). m-Tetra (hydrophenyl)chlorin may be initially retained in the vascular system, possibly due to protein binding or precipitation (Clark and Smith, 1986). This is consistent with plasma binding studies with m-THPC that shows an unusual initial protein-binding pattern for a hydrophobic photosensitiser (Hopkinson et al, 1999).…”
Section: Discussionsupporting
confidence: 67%
“…The plasma levels were initially high (9.37 mg ml À1 ) and appear to declined exponentially as would normally be expected for an intravenous injection. The clearance from plasma, however, did not follow a simple monoexponential decay but could be fitted to multiple exponentials, and because of this the data were analysed by both a noncompartmental and a compartmental approach (Yamaoko et al, 1978;Clark and Smith, 1986). With a compartmental approach, the data best fit a three exponential decay described by the equation C ¼ 5.89 e À1.51t þ 3.36 e À0.1t þ 0.120 e À0.0084t .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent animal studies [8,9] and clinical data [10] have shown that the concentration of sensitizer in the tumor at the time of illumination does not necessarily predict response to PDT. Plasma concentration at the time of illumination is a better indicator for PDT outcome [11][12][13][14]. This suggests that tumor cells may not always be direct targets of PDT, but they may be indirectly killed as a result of damage to other cell types, for example, vascular endothelial cells.…”
Section: Working Mechanism Of Pdt In Vivomentioning
confidence: 99%
“…Furthermore, inhibition of inflammatory responses and vasoconstriction decrease tumor response to PDT, whereas concomitant pharmacological inhibition of angiogenesis enhances the PDT response [11][12][13][14][20][21][22][23][24]. All these studies demonstrate the importance of vascular-mediated damage in obtaining an effective tumoricidal effect after in vivo PDT.…”
Section: Working Mechanism Of Pdt In Vivomentioning
confidence: 99%